[en] THE SOCIAL CONSTRUCTION OF NORMS: THE ORIGIN OF FRAMEWORK CONVENTION ON TOBACCO CONTROL AND ITS IMPACTS ON BRAZIL - LARISSA MENDES MINUSSI (MAXWELL, 2012)
[pt] A dissertação analisa o processo de criação do primeiro tratado de saúde pública internacional, a Convenção-Quadro para o Controle do Tabaco (CQCT), assinada em 2003, e em vigência desde 2005. A hipótese defendida é a de que as décadas anteriores à criação da CQCT coincidem com o estágio de emergência da norma internacional de controle do tabaco – uma denominação avançada pelo presente trabalho na tentativa de sintetizar sob um único conceito analítico uma miríade de ideias, entendimentos, e prescrições internacionais relativas ao controle do tabaco desenvolvidas ao longo das últimas cinco décadas. Nesta perspectiva, a criação da CQCT corresponderia à institucionalização da norma de controle do tabaco a nível internacional. Ainda, tal institucionalização representaria um ponto de ruptura no processo mais amplo de evolução da norma internacional de controle do tabaco, delimitando o início de uma nova fase, caracterizada pela dinâmica de socialização da norma, bem como pela ocorrência de um efeito cascata, em que mais países passam a adotá-la, e de maneira mais rápida. No intuito de analisar o processo de internalização da norma internacional em questão, o trabalho seleciona o caso brasileiro, atentando para como as particularidades domésticas dos países tanto ditam o passo da evolução desta norma, como determinam suas futuras possibilidades. === [en] The scope of this study is to analyze the creation process of the first international public health treaty, the Framework Convention on Tobacco Control (FCTC); which was signed in 2003 and came into force in 2005. The hypothesis is that the previous decades, before the creation of FCTC, overlap with the stage of emergence of an international norm on tobacco control – a denomination used in this present analysis as an attempt to synthesize, under a single analytical concept, the myriad of ideas, understandings, and international prescriptions about tobacco control; which has been developed during the last five decades. In this perspective, the creation of FCTC would correspond to the institutionalization of tobacco control norms at the international level. Furthermore, this institutionalization would represent a tipping point in the whole evolution process of the international norm on tobacco control. This would set the limits of the beginning of a new stage, characterized by the dynamic of socialization of the norm; as well by the occurrence of a cascade effect, where more countries start to adopt the norm and do it in a faster way. With the purpose of analyzing the internalization process of the international norm in question, the present study selects the Brazilian case; emphasizing how domestic particularities of different countries dictate the speed in which this norm evolves, and also determine future possibilities.